Evaluation of the Effects of Five Mold Temperature Variations on Cooling Rate and Contraction Force in the Forming of Aluminum 7075 Alloy - Pratama, Muhammad David (Journal of Engineering and Science, 2024)
The 7075 series aluminum alloy, renowned for its tensile strength of up to 572 MPa, is widely employed in the production of aircraft components requiring exceptional structural integrity, such as wing panels, tail assemblies, fuselage frames, and stringers. The airframe, serving as the primary load-bearing structure, is critical in distributing stresses during both flight and ground operations. This study examines the influence of mold temperature variation on thermal contraction and applied force in 7075 aluminum alloy, using the Constrained Rod Casting (CRC) method. Five mold temperature settings—150 °C, 200 °C, 250 °C, 300 °C, and 350 °C—were analyzed to determine their relationship with cooling rate. Data were obtained through cooling curve observations, followed by curve analysis to extract relevant parameters. The results indicate that the fastest cooling rate occurred at 350 °C (25.1 °C/s), while the slowest occurred at 200 °C (13 °C/s). The highest thermal contraction was recorded at 350 °C (316.54 N), whereas the lowest was observed at 150 °C (252.35 N). Variations in cooling rates are attributed to differences in both mold temperature and the duration of the solidification process.